Feasibility investigation on using silver nanorods in energy saving windows for light/heat decoupling. (15th April 2022) - Pu, Jihong; Shen, Chao; Yang, Shaoxin; Zhang, Chunxiao; Chwieduk, Dorota; Kalogirou, Soteris A.
Abstract: Metallic nanoparticles exhibit localized surface plasmon resonance, which gifts them with enhanced solar energy absorption in a special band. With an adjustable plasma resonance band from the visible light to the infrared, silver nanorods (AgNRs) are potential candidates for energy saving application. In this research, the optical properties of AgNRs were investigated by the Discrete Dipole Approximation ( DDA ) approach, and the spectral response of AgNR/PMMA nanocomposites were studied by a Monte Carlo method. Meanwhile, the ideal window for high luminous transmittance and high thermal radiation insulation was identified, and then eight hybridizations of AgNRs were proposed to match the ideal window. Based on these eight hybridizations, related performance comparisons were conducted. The cases study shows that when the diameter of AgNRs decreases from 30 to 10 nm, both the radiation shielding performance and luminous transmittance can be improved. While as the diameter of AgNRs decreases from 10 to 5 nm, there are insignificant changes in radiation shielding performance or luminous transmittance. The optimal AgNR/PMMA nanocomposites proposed in this study were demonstrated to be positive solutions for light/heat splitting, as they can ensure higher luminous transmittance than 50%, while blocked the solar radiation by about 80%. Highlights: DDA approach coupled with Monte Carlo method was developed to calculate spectral response. The band of 483–640 nm was clairfied as the ideal window for light/heat splitting of sunlight. Sunlight filtered by AgNR/PMMA nanocomposite could reach a luminous efficiency of ∼ 300 lm/W. Properly blended AgNRs have better light/heat decoupling performance than ATO, ITO or CWO.